Stimulated by heating-up changes of lux-brightness characteristics of semi-in sulating speciallyundoped GaAs crystals - Litovchenko, N.M.; Prokhorovich, A.V.; Strilchuk, O.N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2001)
It was shown that thermal treatment of semi-insulating specially undoped gallium arsenide leads to significant changes of lux-brightness characteristics of inter- impurity and impurity bands in the spectra of impurity luminescence. The indicated changes are due to transformations in the system of non-radiating channels of hole recombination in it that took place in the process of thermal treatment. The effect observed can lead to variation of the correlation between the intensities of bands in the spectrum of impurity photoluminescence even if the change of concentration of luminescence centers does not occur. Such changes in lux-brightness characteristics of impurity bands should be concerned while using photoluminescence spectra for the analysis of changes occurring in impurity-deficient composition of gallium arsenide during its thermal treatment.